-3(-6v+4)-8v=4(v-4)-6

Simple and best practice solution for -3(-6v+4)-8v=4(v-4)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-6v+4)-8v=4(v-4)-6 equation:



-3(-6v+4)-8v=4(v-4)-6
We move all terms to the left:
-3(-6v+4)-8v-(4(v-4)-6)=0
We add all the numbers together, and all the variables
-8v-3(-6v+4)-(4(v-4)-6)=0
We multiply parentheses
-8v+18v-(4(v-4)-6)-12=0
We calculate terms in parentheses: -(4(v-4)-6), so:
4(v-4)-6
We multiply parentheses
4v-16-6
We add all the numbers together, and all the variables
4v-22
Back to the equation:
-(4v-22)
We add all the numbers together, and all the variables
10v-(4v-22)-12=0
We get rid of parentheses
10v-4v+22-12=0
We add all the numbers together, and all the variables
6v+10=0
We move all terms containing v to the left, all other terms to the right
6v=-10
v=-10/6
v=-1+2/3

See similar equations:

| 4(3-59)=-5(3p-4) | | m/6-3=2/9-m | | 4x+2+35+70=108 | | 18f-12=19f | | 150x-150=42 | | n+4=9-2n | | 0.87m-0.5=0.18+5 | | x²-21=4x | | 4x+18=-6x-22 | | 8x+12=3x+4 | | 17p-12=16p | | 6x-37=8x-99 | | 4(7x-1)+3(2-5x)-4(3x+3=6 | | 19.8r+17.95+18.6=-15.2r-19.45 | | x×x-21=4x | | -9-23=9p-7p | | -2x-5+3x=2 | | -k+6(k+1)=4k | | 72/n=80 | | 4p-8(-4-8p)=508 | | 3x+2+127=180 | | -1x+(3-x)=2x-7 | | 2/3x+1/4x=2 | | 5m/8-6/8+3m/8=@/8 | | 3/4=x-3/8 | | 4.5(x-9)=2.96 | | 7x=x-870 | | 6x-37+8x-99=180 | | -9.04-3(0.2q-1)=-18.28 | | 3+2x+-1x+-1=3x+-6 | | 1.5^x=3.72 | | –1.6p=8 |

Equations solver categories